2014
DOI: 10.1093/ejo/cju024
|View full text |Cite
|
Sign up to set email alerts
|

Do we need primer for orthodontic bonding? A randomized controlled trial

Abstract: Study was not registered on external databases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 35 publications
2
18
1
Order By: Relevance
“…These results are in line with previous study, which also found significant differences between the groups with and without adhesives 13 . However, a recent study showed that brackets fixed without adhesive presented a debonding rate after 12 months similar to that of brackets fixed with adhesive 15,16 . Other study showed that the penetration of the liquids into narrow capillaries, such as microporosities of etched enamel was influenced by properties of the liquid, such as viscosity and the surface free energy of the capillary wall 17 .…”
Section: Discussionmentioning
confidence: 94%
“…These results are in line with previous study, which also found significant differences between the groups with and without adhesives 13 . However, a recent study showed that brackets fixed without adhesive presented a debonding rate after 12 months similar to that of brackets fixed with adhesive 15,16 . Other study showed that the penetration of the liquids into narrow capillaries, such as microporosities of etched enamel was influenced by properties of the liquid, such as viscosity and the surface free energy of the capillary wall 17 .…”
Section: Discussionmentioning
confidence: 94%
“…With the enamel-etching technique introduced by Buonore, 1 direct bonding of orthodontic accessories, which used to be welded to metal bands, became possible. 1 Direct bracket bonding to dental enamel has been studied over the years, and evaluation of bonding systems and different types of enamel surface preparations prior to bonding 2 - 5 has been conducted in an attempt to improve and obtain adequate bond strength in Orthodontics. 2 , 3 , 6 - 9 …”
Section: Introductionmentioning
confidence: 99%
“…us, according to Nandhra at al. [31], the results of this investigation may only be attributed to that clinician. Also, due to a clearly visible difference in colour between stainless steel and ceramic brackets, neither the operator nor the patient could have been blinded in terms of the type of brackets used during the treatment.…”
Section: Discussionmentioning
confidence: 89%
“…e evidence in relation to the patient's gender and bracket survival is ambiguous. Numerous researchers reported no difference in the bracket failure rate between males and females [15,24,27,31,37,41,42,47,48]. On the other hand, Koupis et al [49], Hammad et al [41], and Jung [29] reported a significantly higher failure rate in males than females, whereas Bazagrani et al [32], who examined the bracket failure rate among adolescents, found that detachments of brackets in boys occurred four times more frequently than in girls.…”
Section: Discussionmentioning
confidence: 99%